MENGUKUR KINERJA KEUANGAN PERUSAHAAN DENGAN PENDEKATAN ANALISA BALANCE SCORECARD (STUDI KASUS PADA PT X JAKARTA) - Siswandi Siswandi (JURNAL LENTERA BISNIS, 2018)
ABSTRACTIn the face of an increasingly complex business environment such as currently requirred method of performance measurement that can assess the company’s performance accurately and comprehensively. In this case the method can be used is the Balance Scorecard. Balance Scorecard is a performance measurement tool that combines measures of financial and non financial performance. Balance Scorecard measures the performance from four perspective, namely learnig and growth perspective, internal business process perspective, customer perspective, and financial perspective.The research was conducted by using data in 2015-2016 at PT  X  to analyze the financial perspective, while for other perspectives analyzed through calculation questionnaire. The population in this study is to customers and employees of PT X   whereas samples taken each is 100 respondents for the employees and the 100 respondents to the customer. Questionnaire have been tested for validity and reliability. Indicator used in this study consisted of ROI, profit margin, operating ratio, customer satisfaction, innovation, and employee satisfaction. From the results of the analysis conducted, it is known that the performance of PT X is pretty good overall. In the financial perspective indicators ROI, profit margin, and operating ratio has shown considerable performance. For the customer perspective showed a good performance in the presence of customer satisfaction that is quite satisfactory. On the internal business perspective, companies can already do agood innovation. And for learning and growth perspective shows the level of employee satisfaction that is quite satisfactory. From the study’s data can be concludeed that by using the Balance Scorecard to provide a more structured and comprehensive.  Keywords: Balanced Scorecard, performance measurement